Upaya Nation Branding Qatar melalui Event FIFA World Cup 2022 - Iswanto, Reza Ramadhani (Global and Policy Journal of International Relations, 2023)
ABSTRACT Qatar is a rich country in the Middle East region which is one of the largest oil producers in the world. In 2008, Qatar inaugurated the Qatar National Vision 2030 (QNV 2030) which aims to transform Qatar into a developed country. To realize this Vision, Qatar is increasingly aggressively presenting itself to the international community. One of them is in 2010, Qatar won the bidding to host the 2022 FIFA World Cup by defeating other countries such as Japan, South Korea and the United States. The bidding victory made Qatar the first Middle Eastern country to successfully host the 2022 FIFA World Cup and became one of the efforts to realize QNV 2030. Various rejections arose after Qatar was chosen to host the 2022 FIFA World Cup due to Qatar's policies that were considered burdensome to participants to the issue of labor exploitation and migrant workers that occurred during the preparation of the 2022 FIFA World Cup. By hosting the 2022 FIFA World Cup, Qatar is trying to improve its image in the international world and convince other countries that they are ready to host the 2022 FIFA World Cup through the implementation of nation branding efforts including policy, investment, tourism, culture and people.Keywords: Qatar, FIFA World Cup 2022, nation branding Qatar merupakan negara kaya di Kawasan timur tengah yang menjadi salah satu penghasil minyak terbesar di dunia. Pada tahun 2008,Qatar meresmikan Qatar National Vision 2030 (QNV 2030) yang bertujuan untuk mengubah Qatar menjadi negara maju. Untuk mewujudkan Visi tersebut, Qatar semakin gencar memunculkan diri ke dunia internasional. Salah satunya adalah pada tahun 2010, Qatar memenangkan bidding untuk menjadi tuan rumah FIFA World Cup 2022 dengan mengalahkan negara – negara lain seperti Jepang, Korea Selatan dan Amerika Serikat. Kemenangan bidding tersebut menjadikan Qatar sebagai negara di Kawasan Timur Tengah pertama yang berhasil menjadi tuan rumah FIFA World Cup 2022 dan menjadi salah satu upaya untuk mewujudkan QNV 2030. Berbagai penolakan muncul pasca Qatar terpilih menjadi tuan rumah FIFA World Cup 2022 dikarenakan kebijakan – kebijakan Qatar yang dirasa memberatkan peserta hingga isu ekploitasi buruh dan pekerja migran yang terjadi selama persiapan FIFA World Cup 2022. Dengan menjadi tuan rumah FIFA World Cup 2022 ini, Qatar berusaha untuk memperbaiki citra di dunia internasional dan meyakinkan negara lain bahwa mereka siap menjadi tuan rumah FIFA World Cup 2022 melalui implementasi upaya – upaya nation branding antara lain policy, investment, tourism, culture dan people. Kata Kunci: Qatar, FIFA World Cup 2022, nation brandingDOI: https://doi.org/10.33005/jgp.v11i02.4195